On the occurrence of the genus Schellencandona (Ostracoda, Candonidae) in Italy, with the description of a new species - Rossetti, Giampaolo; Mazzini, Ilaria; Bruno, Maria Cristina (Zootaxa, 2025)
Subterranean environments harbour a diverse yet understudied ostracod fauna, particularly within the family Candonidae, which poses significant taxonomic challenges due to subtle morphological traits that require careful examination to differentiate genera and species. The genus Schellencandona, composed predominantly of stygobiotic species, currently includes 15 described species, many of which are endemic, while a few may have potential intercontinental distributions. This genus is characterized by considerable variability in the morphology of valve and carapace, along with homoplastic similarities to other subterranean candonid species. In contrast, the morphology of the soft parts is highly conservative across species, offering a more stable basis for taxonomic identification. This study reports the first confirmed records of living Schellencandona species in Italy, including one species new to science, for which a detailed morphological description of both valves and soft parts is provided. The second recorded taxon closely resembles a species previously reported from Germany and more recently from Turkey. Both species were collected from the interstitial habitats of hydrologically-dynamic river stretches and exhibit highly localized distributions. These findings suggest that Schellencandona may have a greater species diversity than currently recognized in Italy, where research on ostracods inhabiting groundwater and groundwater-dependent ecosystems remains limited compared to other European countries. In addition, this study provides a comprehensive review of the literature concerning the geographical distribution and habitat preferences of Schellencandona species. However, the potential to explore biogeographic patterns within the genus remains constrained by the general lack of illustrations accompanying existing records, which hinders the validation of their taxonomic assignments.